Análisis de la producción de espacio público en la ciudad de Guayaquil en el 2000-2014. Caso: intervención urbana del proyecto Puerto Santa Ana etapa II: Ciudad del Río - Hidalgo Silva, David Gonzalo (2015)
The production of public space in Guayaquil in recent decades has allowed the capitalist accumulation for the benefit of the economic elites. This is possible through the urban development model known as urban regeneration promoted by the municipality in functions and has achieved its legitimization by the public. As a result, urban guidelines on social, cultural and ecological are not priority because the mercantilist and corporate elite interests are placed as priority in urban space for Guayaquil. This is the case of the second stage of Puerto Santa Ana, River City project that reveals the criteria for producing public space within an inclusive rhetoric by the municipality but which in practice is exclusive and elitist. The residentes of Santa Ana´s Hill surrounding the project have been disadvantaged in the real estate project although they have lived for decades on this site.